PENGARUH LEVERAGE TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR HEALTHCARE YANG TERDAFTAR DI BEI PERIODE 2017-2020 - Agustiarini, Suzhmita; Wahyuni, Ika; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The background of this research is because of the unstable economic situation due to the impact of the Covid-19 pandemic. Some of the impacts of the Covid-19 pandemic are the weakening of people's purchasing power, the decline in investment figures in various business sectors and prices that are gradually decreasing. In contrast to other sectors, health products from healthcare sector companies are in fact much needed by the community. Are companies in the health care sector experiencing the same thing as companies in other sectors that experienced a decline in stock prices and a decrease in investment levels while the consumption level of health products increased. The purpose of this study was to examine the effect of Leverage on Stock Return with Profitability as an intervening variable. The population in this study were healthcare sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Leverage has a significant negative effect on Profitability, Leverage has a significant positive effect on stock returns, Profitability has a significant positive effect on stock returns. The results of the hypothesis test of the indirect effect show that Leverage on stock returns through profitability has a significant negative effect.